Urogenital symptoms: prevalence, bother, associations and impact in 22 year-old women of the Raine Study - Stockil, L.; Thompson, Judith; Briffa, K.; Smith, Anne; Beales, Darren; Straker, Leon; O'Sullivan, P.; Jacques, Angela (Springer U K, 2018)
Introduction and hypothesis: Urogenital symptoms are prevalent in older women, but there is little data available on the prevalence, bother, impact and associations with low back pain (LBP), obesity, parity, mental health (MH) and quality of life (QOL) in young women. Our aim was to determine the prevalence, bother and impact of urogenital symptoms and to explore associations with LBP, obesity, parity, MH and QOL in 22 year-old women. Methods: This was a cross-sectional evaluation using data collected from 588 women in the Raine Study, a pregnancy cohort in which participants have been regularly followed up from birth until 22 years. Data was analysed using descriptive statistics, univariate comparisons and linear regression models. Results: Prevalence of urogenital symptoms were stress urinary incontinence (SUI) 6.3%, mixed urinary incontinence (MUI) 11.5%, leakage of drops 5.8%, urge urinary incontinence (UUI) 5.3%, bothersome urinary frequency 41.5%, difficulty emptying 11.8% and urogenital pain 22.9%. Urinary frequency, MUI, difficulty emptying and urogenital pain were most bothersome, whilst difficulty emptying and urogenital pain were associated with greatest impact. Urinary frequency, SUI, leakage of drops, difficulty emptying and urogenital pain were associated with current LBP and LBP ever. Difficulty emptying and urogenital pain were associated with chronic LBP. Urogenital symptoms were not associated with obesity or parity. Women with urogenital symptoms had significantly poorer scores on the Mental Component Score of the Short Form Health Survey (SF)-12 and all aspects of the Depression Anxiety Stress Score. Conclusions: Urogenital symptoms are prevalent in young women, bothersome for some and are associated with LBP, poorer MH and reduced QOL.